7. IDENTITAS DAN KEBIJAKAN LUAR NEGERI: BANTUAN KEMANUSIAAN TURKI KEPADA ETNIS ROHINGYA PASCA KONFLIK KOMUNAL MYANMAR TAHUN 2012-2015 - Ringgo Febriar; Reni Windiani; Mohammad Rosyidin (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
The flow of Rohingya refugee from Myanmar to some neighboring countries was initiallyoverlooked by ASEAN member states. Yet, Turkey which is not a member of ASEAN hadcommitted to help out Rohingya refugee by giving humanitarian aid. This research seeksto explain the impact of Muslim identity on Turkish foreign policy by using constructivistapproach. This research employed qualitative research through which the data wascollected both by primary and secondary sources. This research concluded that Muslimidentity does not determine Turkish humanitarian aid towards Rohingya refugees butrather universal moral and humanitarian values.